Helminth ichthyo-parasitic fauna of a South African Sub-Tropical Lake - Matla, Matsoele Moses (University of Limpopo (Turfloop Campus), 2012)
The diversity of the helminth parasites of fishes in a clear-water, subtropical Lake Tzaneen, in South Africa was investigated. Of the 527 fish specimens sampled approximately 9000 parasites were collected. There are 38 different parasite species discussed comprising 27 Monogenea, 3 Digenea, 4 Cestoda, 3 Nematoda and 1 Acanthocephala. Four new monogenean species are described and these are Dactylogyrus spp. 1 to 4. Three monogenean species are introduced as first records in Africa and these are Actinocleidus fusiformis (Mueller, 1934), Haplocleidus furcatus Mueller, 1937 and Acolpenteron ureteroecetes Fischthal & Allison, 1940. Fourteen monogenean and one acanthocephalan species are discussed as first geographical records for South Africa and these are Gyrodactylus rysavyi Ergens, 1973, Dactylogyrus brevicirrus Paperna, 1973, Dactylogyrus cyclocirrus Paperna, 1973, Dogielius dublicornis Paperna, 1973, Dogielius sp., Schilbetrema quadricornis Paperna & Thurston, 1968, Quadriacanthus aegypticus El Naggar & Serag, 1986, Quadriacanthus clariadis Paperna, 1961, Scutogyrus gravivaginus (Paperna & Thurston, 1969), Cichlidogyrus quaestio Douëllou, 1993, Cichlidogyrus halli Price & Kirk, 1967, Cichlidogyrus sclerosus Paperna & Thurston, 1969, Cichlidogyrus dossoui Douëllou, 1993, Cichlidogyrus tilapiae Paperna, 1960 and Acanthosentis tilapiae Baylis, 1948. Seven species are discussed as first records for their hosts and these are Cichlidogyrus dossoui, Cichlidogyrus halli and Acanthosentis tilapiae on Oreochromis mossambicus; Dactylogyrus sp. 1 on Barbus radiatus and Barbus trimaculatus; Dactylogyrus sp. 2 on Barbus unitaeniatus; Dactylogyrus sp. 3 and Dactylogyrus sp. 4 on Labeo molybdinus. Gyrodactylus rysavyi is the only species with a first site (gills) record. The other monogenean species discussed are Macrogyrodactylus clarii Gussev, 1961, Macrogyrodactylus karibae (Douellou and Chishawa, 1995), Dactylogyrus afrolongicornis afrolongicornis Paperna, 1973, Dactylogyrus allolongionchus Paperna, 1973, Dactylogyrus spinicirrus (Paperna & Thurston, 1968) and Cichlidogyrus philander (Douëllou, 1993). The digeneans discussed are Glossidium pedatum Looss, 1899 and the larvae of Diplostomum van Nordmann, 1832 and Clinostomum Leidy, 1856. The Cestodes discussed are Proteocephalus glanduligerus (Janicki, 1928) Fuhrmann, 1933, Polyonchobothrium clarias Woodland, 1925 and the larvae of Ligula intestinalis Goeze, 1782 and family Gryporhynchidae. The nematodes discussed are Procamallanus laevionchus (Wedl, 1861), Paracamallanus cyathopharynx Baylis, 1923 and larvae of Contracaecum Railliet and Henry, 1912. Monogenea were commonly found on the gills but less on the skin and in the urinary bladder. Digenea were found mainly in the eyes, brain and visceral cavity, with only one species (Glossidium pedatum) present in the intestines of Clarias gariepinus. Cestoda and Nematoda were found in the intestine and body cavity. Only one species of Acanthocephala (Acanthosentis tilapiae) was found in the intestines of Oreochromis mossambicus. No definite seasonal variations of infection and parasite affinities towards the sexes and the sizes of the hosts could be determined. The lake is oligotrophic with the water quality having no influence on the parasite diversity and species richness.
Thesis (Ph.D. (Zoology)) --University of Limpopo, 2012
Keywords: Helminth ichthyo-parasitic fauna; 592.30968; Helminthology